2002
DOI: 10.1046/j.1469-0705.2002.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies of the fetal aortic arch: a novel sonographic approach to in‐utero diagnosis

Abstract: Objective To describe a novel, sonographic approach for in-utero evaluation of normal and abnormal aortic arch. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
152
7
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(178 citation statements)
references
References 17 publications
14
152
7
5
Order By: Relevance
“…Another two had mild symptoms, which improved. Computed tomographic angiography and barium swallow at 2 and 5 years of age showed no significant obstruction Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Gul (2012) 29 Miranda (2014) 28 Razon (2014) 24 Chaoui (2002) 25 Achiron (2002) 2 Patel (2006) 10 Berg (2006) 8 Zidere (2006) 7 Tuo (2009) 9 Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Bronshtein (2011) 30 Gul (2012) 29 Miranda (2014) 28 Razon (2014) 24 Current study Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Bronshtein (1998) 6 Gul (2012) 29 Miranda (2014) 28 Achiron (2002) 2 Patel (2006) 10 Berg (2006) 8 Zidere (2006) 7 Tuo (2009) 9 Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Chaoui (2002) 25 Gul (2012) …”
Section: Cohort Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Another two had mild symptoms, which improved. Computed tomographic angiography and barium swallow at 2 and 5 years of age showed no significant obstruction Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Gul (2012) 29 Miranda (2014) 28 Razon (2014) 24 Chaoui (2002) 25 Achiron (2002) 2 Patel (2006) 10 Berg (2006) 8 Zidere (2006) 7 Tuo (2009) 9 Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Bronshtein (2011) 30 Gul (2012) 29 Miranda (2014) 28 Razon (2014) 24 Current study Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Bronshtein (1998) 6 Gul (2012) 29 Miranda (2014) 28 Achiron (2002) 2 Patel (2006) 10 Berg (2006) 8 Zidere (2006) 7 Tuo (2009) 9 Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Chaoui (2002) 25 Gul (2012) …”
Section: Cohort Studymentioning
confidence: 99%
“…It courses to the right of the trachea, in contrast to the normal left aortic arch (LAA). Its incidence is estimated to be 0.1% 1,2 . Variations of aortic laterality and branching pattern result from abnormal regression of the primordial paired aortic arches during embryonic development.…”
Section: Introductionmentioning
confidence: 99%
“…It can be easily obtained by moving the transducer from the 4-chamber view in a cranial direction. Achiron et al 2 showed that the location of the aortic arch in relation to the trachea can be easily visualized because the fetal airway is normally filled with fluid, allowing sonographic visualization. Yagel et al 8 reported application of the 3-vessel and trachea view, which is transverse in the upper mediastinum slightly cranial to the 3-vessel view described by Yoo et al 7 Integration of the 3-vessel view has been proposed in sequential segmental analysis to diagnose congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few reports of prenatal diagnosis of vascular rings. [1][2][3][4] The typical presentation in postnatal life is stridor. Many times, parents notice noisy breathing from birth that is aggravated by intercurrent upper respiratory infections.…”
mentioning
confidence: 99%
“…The incidence of RAA in the general population is unknown, but a rate of 1/1000 in low‐risk pregnancies has been suggested 56 . It is a normal variant of vascular anatomy.…”
Section: Introductionmentioning
confidence: 99%